2014
DOI: 10.1051/0004-6361/201322481
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of an activated filament in a flaring active region

Abstract: Aims. While the magnetic field in quiescent prominences has been widely investigated, less is known about the field in activated prominences. We report observational results on the magnetic field structure of an activated filament in a flaring active region. In particular, we studied its magnetic structure and line-of-sight flows during its early activated phase, shortly before it displayed signs of rotation.Methods. We inverted the Stokes profiles of the chromospheric He i 10 830 Å triplet and the photospheri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 65 publications
6
26
1
Order By: Relevance
“…4), when the new Hα filament has formed, is consistent with previous such measurements (Lites 2005;Okamoto et al 2008;Lites et al 2010;Xu et al 2012;Sasso et al 2014). At several locations within the PIL higher fields strengths of up to 800 G at log(τ) = −2 can be observed, which appear to be somewhat short lived, since they can never be observed at the same place in consecutive SOT/SP scans.…”
Section: Discussionsupporting
confidence: 91%
“…4), when the new Hα filament has formed, is consistent with previous such measurements (Lites 2005;Okamoto et al 2008;Lites et al 2010;Xu et al 2012;Sasso et al 2014). At several locations within the PIL higher fields strengths of up to 800 G at log(τ) = −2 can be observed, which appear to be somewhat short lived, since they can never be observed at the same place in consecutive SOT/SP scans.…”
Section: Discussionsupporting
confidence: 91%
“…Although the flux-rope model is consistent with many active-region filaments (e.g., Dudík et al 2008;Canou & Amari 2010;Sasso et al 2014;Liu et al 2014aLiu et al , 2016, more complicated magnetic configurations are not rare. For example, Guo et al (2010) found that a flux rope and a sheared arcade match two sections of a filament separately.…”
mentioning
confidence: 66%
“…Leroy et al, 1984;Bommier et al, 1994;Parenti, 2014;Ouyang et al, 2017), the flux ropes with a normal configuration are usually observed in the vicinity of active regions (see e.g. Okamoto et al, 2008;Guo et al, 2010;Kuckein et al, 2012;Sasso et al, 2014), and can be responsible for fast CMEs (Low and Zhang, 2002). The horizontal equilibrium of the prominence in such a magnetic system is provided automatically because of the horizontal symmetry of the model, while the vertical equilibrium is determined by the balance of the gravity force F g and three Lorentz forces F 1 , F 2 , and F m acting on the prominence from the external photospheric and mirror currents, respectively.…”
Section: Model and Governing Equationsmentioning
confidence: 99%